Optimization and microbial community analysis of anaerobic co-digestion of food waste and sewage sludge based on microwave pretreatment. (January 2016) - Zhang, Junya; Lv, Chen; Tong, Juan; Liu, Jianwei; Liu, Jibao; Yu, Dawei; Wang, Yawei; Chen, Meixue; Wei, Yuansong
Highlights: Methane production was enhanced by both co-digestion and MW pretreatment. The optimized ratio was 3:2 for anaerobic co-digestion based on MW pretreatment. Propionic accumulation led to lower methane production of MW-FW compared to MW-SS. Bacteroides only dominated in co-digestion, Methanosphaera only dominated in MW-FW. Methanosarcina was the predominant methanogens for mono-SS and MW-SS. Abstract: The effects of microwave pretreatment (MW) on co-digestion of food waste (FW) and sewage sludge (SS) have never been investigated. In this study, a series of mesophilic biochemical methane potential (BMP) tests were conducted to determine the optimized ratio of FW and SS based on MW, and the evolution of bacterial and archaeal community was investigated through high-throughput sequencing method. Results showed that the optimized ratio was 3:2 for co-digestion of FW and SS based on MW, and the methane production was 316.24 and 338.44 mLCH4 /gVSadded for MW-FW and MW-SS, respectively. The MW-SS was superior for methane production compared to MW-FW, in which accumulation of propionic acid led to the inhibition of methanogenesis. Proteiniborus and Parabacteroides were responsible for proteins and polysaccharides degradation for all, respectively, while Bacteroides only dominated in co-digestion. Methanosphaera dominated in MW-FW at the active methane production phase, while it was Methanosarcina in MW-SS and mono-SS.